Pemberian Dosis Biourine Sapi dan Media Tanam Pada Beberapa Variabel Pertumbuhan dan Hasil Ekonomis Tanaman Pakcoy (Brassica chinensis L.) - Adi Tiya; I Nengah Suaria; Anak Agung Sagung Putri Risa Andriani (GEMA AGRO, 2019)
The purpose of this study was to determine the effect of giving a cow's bio-urine dose and the composition of the planting medium and its interaction on several growth variables and economic yield of pakcoy plants. This research was conducted at the Experiment Station of the Faculty of Agriculture, Warmadewa University. This research activity was carried out in April to June 2018. The experiment consisted of two factors: the first factor was the dose of bio-urine of the cow consisting of 4 levels, namely 0 ml/polybag, 10 ml/polybag, 20 ml/polybag, 30 ml/polybag. The second factor, the planting medium consists of 3 levels, namely soil + cow manure, soil + husk charcoal, soil + sawdust. Experiments are designed with (RAK). Treatment of bio doses of cow urine, planting media, and interactions between bio doses of cow's urine and planting media showed very different. Interaction between 30 ml/polybag of bio urinary cow fertilizer with soil fertilizer + cow fertilizer which gave an economic oven oven dry weight of 7.93 g Â± 0.38 times increased by 79.20% from the lowest 0.01 g Â± 0.38 introduction of interaction when measuring cow's urine urine 0 ml, 10 ml, and 30 ml with soil planting media + sawdust. The use of 30 ml/Polybag bio-urine doses and soil + cow fertilizer can be used for the highest yield and growth of pakcoy plants.